1988
DOI: 10.1084/jem.168.1.95
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance to tumor necrosis factor in rats and the relationship to endotoxin tolerance and toxicity.

Abstract: Treatment of rats with recombinant human TNF initially causes a marked decrease in food intake, a loss of body weight, and a negative nitrogen balance. These alterations normalize with continued twice daily intraperitoneal injections of the same dose. Rats tolerized to TNF in this manner are refractory to a lethal dose of TNF. Also, TNF-pretreated and -tolerized rats have prolonged survival and reversed histopathologic changes after injection of a lethal dose of endotoxin compared with control animals. The TNF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
80
1
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 178 publications
(85 citation statements)
references
References 19 publications
3
80
1
1
Order By: Relevance
“…In contrast to our results, Norton et al [27] demonstrated that TNF-a was capable of inducing tolerance to LPS. This discrepancy could be the result of a different animal model (rat), and/ or the fact that their experiments were carried out using an extremely high, and not physiological, dose of TNF-a (200 mg/kg/day for 5 consecutive days).…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to our results, Norton et al [27] demonstrated that TNF-a was capable of inducing tolerance to LPS. This discrepancy could be the result of a different animal model (rat), and/ or the fact that their experiments were carried out using an extremely high, and not physiological, dose of TNF-a (200 mg/kg/day for 5 consecutive days).…”
Section: Discussioncontrasting
confidence: 99%
“…Tolerance to TNF has been demonstrated in animals, 12 and has been suggested to occur in humans 13 based on the evidence that when tumor patients were treated with TNF-␣, they became refractory to its side effects after repeated exposure. 14 Therefore, the evidence presented in this study, may be the first to support the existence of tolerance to autologous TNF-␣ in humans.…”
Section: Resultsmentioning
confidence: 99%
“…Up-regulation of other putative protective cytokines in untreated transgenic animals or after administration of Con A could also play a role in hepatic protection and remains to be elucidated. Such a cytokine stimulatory network has been reported for the induction of desensitization after repeated administration of endotoxin or TNF to rodents (53)(54)(55)(56). The exact mechanism of cytokine tolerance is not fully understood, but it has been proposed that in desensitized cells alteration of the signaling cascades, rather than down-regulation of the corresponding receptors, plays a role (57,58).…”
Section: Discussionmentioning
confidence: 99%